Sistem Automatic Transfer Switch Syncronous Menggunakan Dua Trafo Sebagai Pemicu LVD dan HVD Pada PLN-PLTS On Grid - Badruzzaman, Rifqi; Irwanto, Irwanto (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
Indonesia is a country that has abundant natural resources with the potential for renewable energy such as sun, water, wind, etc. In the rapid development of technology, of course, the utilization of natural resources that are very abundant is something that must be done. Especially solar power that can be utilized as an efficient and environmentally friendly Solar Power Plant (PLTS). In addition, the utilization of PLTS is as backup power when PLN experiences power outages. Sudden power outages create a lot of unrest and complaints from electricity users, especially those that require continuous electricity supply such as offices and markets in data storage. The solution to the problem is to use the Automatic Transfer Switch Syncrounus system using 2 transformers that work by transferring power automatically without a split second power outageKeyword: Sistem, Switch, Syncronous, Trafo, Transfer